PENINGKATAN HASIL BELAJAR SISWA KELAS IV PADA MATA PELAJARAN PKN MELALUI TEKNIK CERAMAH BERVARIASI SD NEGERI 017989 MANIS - Siti Kholijah (JURNAL TEMATIK, 2020)
the purpose of this study was to improve the learning outcomes of fourth grade students on PKN subjects through varied lecture techniques sweet SD 017989. This type of research is classroom action research using test instruments and observation sheets of 2 cycles. The results showed that student learning outcomes by 65% got a complete value and 35% got an incomplete value with an average value of 69.0 in cycle I. In cycle II student learning outcomes by 90% got a complete grade, and by 10% got an unfinished value with an average rating of 89.0. Thus varied lecture techniques can improve student learning outcomes.